Teachers` understanding of family values: a qualitative survey - Sulaiman, Siti Sa'adah; Jamaluddin, Rahimah; Bakar, Ab. Rahim; Mohd Fakhruddin, Fathiyah; Surif, Johari; Ibrahim, Nor Hasniza (Serials Publications, 2017)
This qualitative case study is aimed to explore teachers' understanding of family values. The respondents consist of five secondary school teachers, who teach five subjects that cover family themes. The process of collecting data is obtained by using semi-structured interviews, observation and document analysis. Issues of validity and reliability of the study are resolved by using four methods, namely triangulation, peer review, audit trail and prolonged engagement. Atlas.ti software is used to analyse the transcription of interviews and develop the theme in this study. The findings show that family values understood by the teachers are in reference to good values, good manners and culture of life. Teachers' understanding of family values is closely related to the aspects of family and community life. Therefore, inculcation of family values should be given priority and attention by all parties, especially teachers and parents.